In cerca di se stesso e degli altri. Il casting di 8 ½ (Fellini 1963) (Mantichora. Italian Journal of Performance Studies, 2020)
It is known that for Federico Fellini selecting actors was a very important moment of the movie preparation. This essay, by analyzing the casting of a very representative film such as 8 ½, wants to explore the rational and irrational ways that led Fellini to choose a certain face instead of another, trying to define the importance of actors, from the main roles to the extras, to the general composition of the film. Part of this research is based on unpublished production documents kept in the Cinema Section fonds of Ministry of Cultural Heritage at Rome Central State Archive.